DEVELOPMENT OF A LEARNING MEDIUM BASED ON EFAS TRADITIONAL GAME (ENGKLEK FUN AND SMART) TO IMPROVE STUDENTS' COMMUNICATION ABILITY IN THEMATIC LEARNING - Zhao, Bin; Anas, Nirwana (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
Traditional games must be adapted for the present since they have cultural values that need to be conserved for future generations. This study attempts to create an EFAS (Engklek Fun and Smart) medium version of a typical game product. With research experience at IES Al-Ittihadiyah Berastagi, this study applies the Research and Development (R&D) technique. Forty-five first graders of Islamic Elementary School (IES) Al-Ittihadiyah Berastagi became the study participants. The findings indicate that the EFAS medium is recognized as valid. The "Very Valid" category showed an 89.63% score for the EFAS medium. It is also claimed that the EFAS medium is useful. This information came from a survey of the students and teachers’ opinions. Twenty-five students completed a questionnaire on the EFAS medium, and the questionnaire received 9.6% in the "Very Practical" category. A score of 97.5% in the "Very Practical" category came from the teachers’ response to the supplied statement. The results of the two questionnaires indicate that the teachers and students’ replies are categorized as being very practical. Third, the EFAS medium is deemed operational. This was demonstrated by the fact that the students were able to respond to the ASK and DO question instruments both in writing and orally with a score of 92% during the learning process utilizing EFAS. Written responses to EFAS infer that it can be an "effective" medium, whereas oral responses indicate that the medium can help students develop their communication abilities. This justifies the declaration that the EFAS medium is legitimate, applicable, and useful for enhancing students' communication skills.